MAPPING THE LEVELS AND SOURCES OF TRANS FATTY ACIDS IN THE MOROCCAN DIET - Lahmam, Houria; El Hajjab, Amina; El Berri, Hicham; Gmouh, Said; Mehdad, Slimane; Benajiba, Nada; Attarassi, Benaissa; Aguenaou, Hassan; Auajjar, Nabila (Malaysian Journal of Public Health Medicine, 2025)
Trans fatty acid (TFA) consumption has been unequivocally associated with several adverse health effects. Consuming TFAs in amounts greater than 2% of total energy intake (TEI) is associated with a 23% increase in cardiovascular risk. The present study aimed to assess the primary levels and sources of TFAs in the Moroccan diet, serving as a first step toward reducing, replacing, or eliminating industrially produced TFAs. A total of 54 samples of local products and major food sources of TFAs (oils [edible oil, frying oil, soybean and sunflower oil, sunflower oil, partially hydrogenated palm and palm kernel oils], shortenings, margarines [pastry and spread], potato chips, cold cuts, pastry, biscuits, breakfast cereals, yogurts, sour cream and chocolate spreads) were collected and analyzed by gas chromatography (GC) to determine the fatty acid composition profile. Fatty acids were then expressed as a percentage of total fat. In the twelve pastry margarine samples, the TFA content was 6.9% and 3.41% for the ten sample of spreadable margarines. In the oil samples, the TFA content ranged from 0.42% (sunflower oil) to 0.81% (edible oil). Shortenings had a TFA content of 42.16%, followed by partially hydrogenated oil (4.06%). For other food products, the average percentage of TFA was 0.01% in pastries, 0.48% in sour cream, 0.27% in potato chips, 0.04% in cold cuts, 0.16% in breakfast cereals, and 0.19% in chocolate spread. Our study provides for the first time an estimate of TFA levels in selected Moroccan food products and support the need to accelerate national efforts to reduce, replace, or eliminate industrial trans fats in the Moroccan diet. These findings could be used as a basis for advocacy for a ban on partially hydrogenated oils.